Формування комунікативної компетентності майбутнього вчителя музики в умовах педагогічного коледжу - Поясок, Тамара; Беспарточна, Олена (Національний технічний університет "Харківський політехнічний інститут", 2019)
Розглянуто структуру і зміст комунікативної компетентності майбутнього вчителя музики; досліджено умови її ефективності та поетапне формування; наведено зміст тренінгу формування комунікативної компетентності майбутніх вчителів музики.

Problem setting. The current state of economic, social and cultural life of society requires certain changes in education, in particular, its structural and substantive updating. Automation and rationalization of different activities, globalization processes in culture increase the role of music education of students. At the same time, music-aesthetic education in educational institutions needs improvement, which necessitates the preparation of a new generation of music teachers. Person-centered education focuses on the dialogic interaction between teachers and students, which can only be realized if communication competence is formed. It should be borne in mind that the students of pedagogical colleges are different from students of pedagogical universities, in particular, they have more difficulties in pedagogical communication. Recent research and publications analysis. I. Stashevs‘ka, O. Rudnits‘ka, O. Oleksiuk, O. Mykhailychenko, O. Gorbenko and others devoted their researches to the problems of professional training of future music teachers. The formation of communicative competence of future music teachers is to some extent reflected in the works of E. Ivanova, G. Padalka, O. Oleksiuk, V. Zamorots‘ka, L. Savenkova, T. Skoryk and others. However, in our view, insufficient attention has been paid to the shaping of the communicative competence of a future music teacher in a pedagogical college. Paper objective. Given the relevance of the topic and the lack of its research, the purpose of the article is to substantiate the method of the communicative competence‘ forming of future music teachers in the conditions of a pedagogical college. Paper main body. Theoretical analysis of the scientific and pedagogical literature shows that the formation of communicative competence of the future music teacher ensures the efficiency and success of his professional activity. Communicative competence is understood as a system of psychological knowledge about oneself and others, communication skills, a strategy of behavior in social situations that allows building effective communication in accordance with the goals and conditions of professional and interpersonal interaction. The structure of communicative competence contains such components as cognitive, emotional and behavioral. The cognitive component implies knowledge about the psychological characteristics of communication, knowledge of communication partners. The emotional component is the very attitude and attitudes of communication, while the behavioral component is the system of communicative skills, abilities and qualities of the individual. In our opinion, the formation of communicative competence of future music teachers in the conditions of a pedagogical college should be carried out consistently: organization of communication, development of communicative abilities, and formation of communicative skills. It is advisable to carry out the work on formation of communicative competence of future music teachers in psychological (individual consultations, group trainings, extracurricular activities) and pedagogical (introduction of specific methods and techniques aimed at the development of communicative competence for each discipline of psychology) directions. The forming of the communicative competence of future music teachers in a pedagogical college should be based on a systematic approach that will make the process purposeful and optimally managed. The main condition for achieving this goal is the targeted orientation of the educational process and, in particular, of professional disciplines for the preparation of future specialists for communication activities and their inclusion in the system of subject-subject relations in communication. Professional disciplines have considerable didactic potential for engaging students in professionally directed communication and in the formation of professionally meaningful ways of communicative music teacher culture.Integration of the content of the pedagogy course, special course and practice requires strengthening of the cultural aspect of pedagogical knowledge and theoretical studies on communicative culture. The training special course is aimed at forming the professional competence of students in the field of communication and communicative ways that allow regulating the nature of interaction with students and colleagues. Students must learn how to anticipate situations, be prepared to regulate interaction, achieve emotionally positive results, and accept each other. Only when the principles, organization and content of learning are presented in didactic unity and interdependence, the pedagogical theory becomes the driving force of the learning process. The development of the theoretical foundations of the content of communicative music teacher training and the study of specific methods of its formation should complement each other. Formation of the communicative competence of the future music teacher involves, first of all, the development of technique and culture of speech, speech abilities, such as verbal memory, expediency of speech means, logical expression, orientation to the interlocutor, adequate emotional diversity of speech, lexical variety etc. The student's cognitive interest in music is enhanced by the teacher's emotionally rich narrative that creates a setting for its perception, stimulates interest in listening to music, and reflecting on the music. Along with the verbal communication, non-verbal communication plays an important role in communication of the music teacher that provides the comfort of music lessons. Future music teacher‘s preparing in a pedagogical college to communicate effectively requires the development of interconnected communication skills and skills that need special education. For this purpose, it is advisable to introduce group training that is based on the use of active methods of group work in order to develop competence in communication and aimed at the achieving of the practical results.Conclusions of the research. Changes in the current educational process require a profound mastery of communicative skills from a future music teacher. In the practice of music teacher the communicative competence is manifested in the creative approach to the lessons. What he wants to teach should not be dictated but jointly rediscovered, involving students in the active work. The student should feel that the teacher is talking to him as with an equal. Then he will have confidence in the teacher and he will have a sense of responsibility, a desire to justify that trust. Communicative competence is an important feature of competence of a future music teacher. An important indicator of his competence in communication is the attitude to his own values: the way he reflects them. The use of different forms and methods of joint activity of teachers of teacher training (pedagogical) college with future music teachers will allow optimizing the process of formation and development of communicative competence of students. The pedagogical mechanism of formation of communicative competence of future music teachers is based on the dialogue of pedagogy and culture, teacher and student. It involves the interaction of the content of pedagogical disciplines, special courses and pedagogical practice that is learned by students through problematic discussions, multi-vector dialogues, reflexive analysis and assessment, pedagogical improvisations, training and play exercises. Pedagogical practice is considered as an environment of the practical application of students' acquired communication skills. This study does not exhaust all the aspects of communicative competence formation of a future music teacher in a pedagogical college.
Formation of communicative competence of a future music teacher in the conditions of the pedagogical college
Keywords: тренінг; інноваційні засоби навчання; training; innovative training tools